THE PURPOSES AND CHALLENGES OF SUPPLEMENTARY HEARINGS IN THE CRIMINAL PROCEDURE CODE OF THE REPUBLIC OF ARMENIA - Ghazinyan, Gagik; Hovhannisyan, Lusine (State and Law, 2025)
This article examines the newly introduced institution of supplementary hearings in the Criminal Procedure Code (CPC) of the Republic of Armenia, in force since 1 July 2022. Focusing on supplementary hearings held after a guilty verdict, it explores the legislature’s aims, the mechanism’s doctrinal foundations, and implementation challenges. Drawing on comparative criminal-procedure (United States, United Kingdom) and interdisciplinary findings from psychology and behavioral science, the authors argue that a bifurcated model that separates adjudication of guilt from sentencing decisions is valuable even without a jury, because it mitigates cognitive biases, particularly confirmation and hindsight bias, that can otherwise contaminate punishment. While the CPC’s tripartite structure (preliminary, main, supplementary hearings) aspires to balance public and private interests, current rules permit character and sentencing-related materials to surface during the main hearing, weakening the intended procedural barrier. The article proposes targeted reforms to operationalize the separation: (i) amend Article 102 to allocate facts strictly between the main hearing (event, attribution, elements, guilt) and the supplementary hearing (aggravating/mitigating factors, character, harm, civil claims); (ii) introduce a “two-envelope” mechanism requiring the prosecution and parties to submit guilt-related and sentencing-related evidence in separate sets; and (iii) revise Article 319 to bar the submission or examination of character/sentencing evidence before the verdict. Alternatives such as different judges for verdict and sentence are noted but assessed as impracticable. Properly implemented, supplementary hearings can more effectively safeguard fundamental rights and enhance the legitimacy and accuracy of sentencing in Armenia’s criminal justice system.